CONCEPT OF CONTROL SYSTEM FOR HYBRID ELECTROMAGNETIC LAUNCHER WITH USE OF REAL TIME CONTROLLER - Makowski, Tomasz (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2017)
The article describes concept of an integrated control system for the hybrid electromagnetic launcher. The main issue of the concept control system is to use a real-time controller (CompactRIO-9022) playing additionally role of a measurement system. The control system will be connected to LAN network, which allows to remote control of launcher. In article used controller is described specifically also with available extension and LabView software.